O wierności. O pracy nad przekładem tekstów Olgi Tokarczuk z Yi Lijun – tłumaczką literatury polskiej na język chiński – rozmawia Zhao Zhen - Yi Lijun; Zhao Zhen; Michał Kumor (Postscriptum Polonistyczne)
Translations into Chinese by Professor Yi Lijun, a distinguished translator of Polish literature, include the most popular books by the most recent Nobel Prize winner Olga Tokarczuk: Primeval and Other Times and House of Day, House of Night. During the interview, the Professor shares, for the first time, her experiences and interesting stories that happened between the translator and the writer. This allows us to find out what brought the writer’s novels success among Chinese readers.